Assessing the Diagnostic Utility of FDG-PET and HPLC for Detecting Microglia Activation and Inflammation in Alzheimer’s Disease - Sayed Mehrdad Azimi; Mohammadreza Elhaie; Iraj Abedi; Hossein Salehi (Advanced Biomedical Research)
Early and accurate Alzheimer’s disease (AD) diagnosis is essential due to its progressive nature and significant impact. This study reviews and analyses FDG-PET and HPLC techniques in detecting inflammation and microglia activation in AD, marking the first comparison of their diagnostic capabilities. Through a literature search of publications from January 2021 to December 2023 across Scopus, Science Direct, and PubMed databases, 31 relevant articles were selected for analysis. FDG-PET and HPLC data on sensitivity, specificity, and inflammation were examined, highlighting their roles in detecting amyloid plaques, microglial activation, and blood/CSF metabolite regulation. Although amyloid PET offers higher sensitivity, FDG-PET uniquely classifies cognitive stages in AD despite its limitations due to glucose metabolism variance. Whereas HPLC provides insight into metabolic profile changes, it is noted for being invasive and costly. The combined use of FDG-PET and HPLC promises a comprehensive AD diagnostic approach by offering unique, complementary insights into functional and molecular brain changes. However, further validation is needed to overcome technical challenges and confirm their effectiveness before widespread adoption. The advancement of these diagnostic tools, alongside ongoing research, could significantly improve early AD detection, monitoring, and treatment. This review provides a novel assessment and comparison of the diagnostic utility of FDG-PET and HPLC techniques for detecting neuroinflammation and microglia activation in Alzheimer’s disease by analyzing relevant studies between 2021 and 2023, highlighting their complimentary strengths and limitations.